PENGELOLAAN VENUE PEKAN OLAHRAGA NASIONAL (PON) XVIII PROVINSI RIAU TAHUN 2012 DILIHAT DARI PERSPEKTIF DESENTRALISASI - Safitri, Ria; ", Erman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This study is motivated by the delivery to the Pekan Olahraga Nasional-XVIII in Riau Province in 2012 as the host. Sports grand party in Indonesia has left a lot of problems and homework for Riau province and demanded to be resolved. The problem is quite important is the management of the venue which is used in various sports in Pekan Olahraga Nasional-XVIII. The Government has developed the initial concept for the management of post-execution venues to the Pekan Olahraga Nasional-XVIII. The concept is structured in line with the start of construction of venues, both new construction and rehabilitation of buildings venue preexisting buildings. But the facts on the ground indicate that the concept of management is not carried out in accordance with the concept that has been arranged from the beginning. Many venues that stay dormant in the sense not maintained and utilized. Based on this background , the study aims to find out how the venue budgetary policy of the Pekan Olahraga Nasional (PON) XVIII in Riau Province in 2012 and how the management of the venue after the implementation of the Pekan Olahraga Nasional (PON) XVIII Riau Year in 2012. This research is a descriptive study, the research aims to describe in a systematic, timely and reliable on the whole subject or object in the present study is based on the facts that appear. Method of data collection with interviews, field observation and documentation search. The results showed that the Riau provincial government has developed a number of policies with respect to venue construction budget of the Pekan Olahraga Nasional (PON) XVIII Riau Province in 2012 as outlined in several regulatory regions of Riau Province. The government has also made efforts to manage the venue to the Pekan Olahraga Nasional-XVIII but not entirely. Management is also not done in accordance with existing rules and concepts that have been developed previously. While there are obstacles that arise in the management process is done, the problem of availability of funds, limited human resources/implementers, and the disclosure of corruption cases involving officials in the government critical of Riau province. Keywords : Decentralization , Fiscal Decentralization , Asset Management , PON XVIII/2012